Tingkat Pengetahuan dengan Sikap Remaja terhadap Pendewasaan Usia Perkawinan - Oktarianita Oktarianita; Bintang Agustina Pratiwi; Henni Febriawati; Padila Padila; Andry Sartika (Jurnal Kesmas Asclepius, 2022)
This study aims to determine the level of knowledge with adolescent attitudes towards Maturation Age of Marriage (PUP). This research method is a quantitative research with a cross sectional approach. The results showed that there were 63 female adolescents (63%), the most aged 18-19 years 51 (51%), good knowledge 65 people (65%) and a positive attitude of Maturation of Marriage Age (PUP) namely 61 people (61 %). In conclusion, there is no relationship between the level of knowledge with adolescent attitudes towards Maturation Age of Marriage. Keywords: Age of Marriage Maturity, Adolescents, Attitudes, Knowledge Level